Forest restoration shows uneven impacts on soil erosion, net primary productivity and livelihoods of local households. (January 2022) - Xu, Jiaoyang; Zhang, Yangyang; Huang, Chunbo; Zeng, Lixiong; Teng, Mingjun; Wang, Pengcheng; Xiao, Wenfa
Highlights: Forest restoration programmes in China have targeted ecosystem services and livelihoods. Forest restoration programmes have improved key ecosystem service indicators. The key ecosystem services of the persisting forest are irreplaceable. Forest restoration programmes have not had a negative impact on livelihood. The inequalities of livelihoods among households may lead to a resurgence of deforestation. Abstract: China has made tremendous efforts in forest restoration (FR), and has established ambitions to govern its fragile ecosystem and improve green welfare until 2035. However, debate still exists over whether FR can simultaneously improve ecosystem services and enhance livelihoods. In this paper, we test the impacts of forest restoration on key ecosystem services and livelihoods via a case study of Badong County in the TGRA, China. The Revised Universal Soil Loss Equation and Carnegie-Ames-Stanford Approach were used to evaluate the soil erosion rate (SER) and net primary productivity (NPP), and we analyzed livelihoods through 520 surveys. Our results revealed that forestland increased significantly from 45.34% to 69.63% during 1990–2015. The annual average SER significantly dropped from 67.01 to 51.18 t·ha −1 ·yr −1 during 2001–2015, and the annual average NPP increased from 547.12 gC·m −2 ·a −1 in 2000 to 609.81 gC·m −2 ·a −1 in 2015. However, the afforestation area offered disadvantages when compared with the persisting forest area in SER and NPP. Households in ecologically fragile areas have equal opportunities in, among others, infrastructure and government policies, but their income and living conditions are often heterogeneous. The per capita income and area of residence improved under FR. Nonetheless, the inequality in per capita income between participating households (PHs) and nonparticipating households (NPHs) increased. Compared with NPHs, PHs lost more cropland, and agricultural income, and more PH householders were forced to find new livelihood activities. These inequalities are not conducive to the sustainable development of FR. Accordingly, we recommend that restoration efforts should focus on forest quality and habitat availability improvement in the persisting forest area and afforestation area, and on new reforestation programmes where appropriate. The government should provide sustainable and science-based ecological subsidies and help PHs obtain alternative livelihood activities, which contribute to higher household income and poverty alleviation.